AB0522 Tacrolimus in refractory lupus nephritis: a prospective multicentric study carried out in clinical practice setting. (12th June 2018) - Larosa, M.; Zen, M.; Iaccarino, L.; Tincani, A.; Andreoli, L.; Conti, F.; Spinelli, F.R.; De Marchi, G.; De Vita, S.; Doria, A.
Abstract : Background: The efficacy of tacrolimus (TAC) in lupus nephritis (LN) has been recently demonstrated in several randomised controlled trials in asian cohorts. 1 Nevertheless, data on real-life experience and long-term safety of TAC are still lacking. Objectives: To assess efficacy and safety of TAC in SLE patients with refractory LN in a multi-centric prospective cohort. Methods: Adult SLE patients with refractory LN from 4 Italian centres were prospectively followed for at least 12 months. Clinical and serological variables and previous/concomitant medications were collected at baseline, 3, 6, 12 months after starting TAC. Renal response was assessed by using EULAR/ERA-EDTA definitions. 2 Adverse events (AEs) included non-infectious and infectious AEs; they were defined severe (SAE) when hospitalisation and/or death and/or life-threatening manifestations occurred. Data were analysed using SPSS (v.24.0). Results: Thirteen SLE patients (8 females, 5 males, mean age 33.7±10.2, mean disease duration 11.9±5.9) were enrolled (table 1). Concomitant medications included: prednisone(100%), mycophenolate mofetil(92.3%), hydroxychloroquine(53.8%), azathioprine(7.7%), belimumab(7.7%) and cyclosporine(7.7%). The average number of previous immunosuppressants taken by each patient was 3.15±1.90. Six-months renal response was achieved by 5/13 patients (38.5%): complete renal response (CRR) in 3 (60.0%) and partial renal response (PRR) in 2 patients (40.0%). Twelve-months renal response occurred in 4/13 patients (30.8%): CRR in 2/13 (50.0%) and PRR in 2/13 (50.0%). One patient achieved CRR at 6 and 12 months; one patient achieved PRR at 6 months and CRR at 12 months. Six patients (46.1%) discontinued TAC after an average follow up period of 10.2±7.8 months. Causes of discontinuation were: 3 non-infectious non-SAEs, 1 flare, 1 non-infectious SAE, and 1 non-response. Concerning AEs, no severe infections or deaths occurred. Conclusions: Our preliminary data from clinical practice setting suggest that TAC could be a therapeutic rescue strategy for refractory LN. Further studies are needed to prove TAC efficacy in the long term. References: [1] Mok CC, Ying KY, Yim CW, et al. Tacrolimus versus mycophenolate mofetil for induction therapy of lupus nephritis: a randomised controlled trial and long-term follow-up. Ann Rheum Dis2016;75:30e6. [2] Bertsias GK, Tektonidou M, Amoura Z, et al. Joint European League Against Rheumatism and European Renal Association–European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations for the management of adult and paediatric lupus nephritis. Ann Rheum Dis2012;0:1–12. Disclosure of Interest: None declared